Hubungan Tingkat Stres dengan Gejala Vaginitis pada Mahasiswi Program Studi Kedokteran FK UNAND 2019 - Megawati, Melsi; Adnani, Syahredi Syaiful; Rahman, Sukri (Andalas Obstetrics And Gynecology Journal, 2020)
Objective: determine the relationship between stress levels with symptoms of vaginitis in medical students at the Faculty of Medicine, Andalas University batch 2019.Method: was observational analytic with cross-sectional approach. Sampling was conducted by non-probability sampling. The sample was 140 by conducting a guided interview on 140 female students of the Medical Education Faculty of Andalas University batch 2019. The stress level of the female students was measured by a stress questionnaire from the Depression Anxiety Stress Scale (DASS 42) and vaginitis symptoms questionnaire. Data analysis used Chi-Square test.Result: more than half of respondents which is 71 respondents (50,6%) has stress. Then, moderate stress levels is the largest percentage, that is 31 respondents (43,6%). Most respondents, 121 respondents (86.4%) have experienced symptoms of vaginitis. The statistical test results obtained p-value = 0.943.Conclusion: more than half of repondents has stress and most respondents have experienced symptoms of vaginitis. The p-value showed that there is no significant relationship between stress levels and symptoms of vaginitis.Keywords: Stress, vaginitis, adolescent